TINJAUAN HASIL TES KETERAMPILAN TEKHNIK DASAR SEPAKBOLA PADA TEAM SMPN 2 BENGKALIS KECAMATAN BENGKALIS - Evendi Evendi; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, type of research is descriptive with the purpose of providing a systematic overview of the state of the ongoing research on the object of population in this study are all the players on Team Ball at SMPN 2 Bengkalis District of Bengkalis the number of players as many as 28 people. The sample in this study amounted to as many as 28 people. Further data analysis techniques using deskriktif analysis to test the ability menggunakakn basic techniques of football. Based on the above data processing results can be in the know that the Basic Technical Skill Level Football Team SMPN 2 Bengkalis District of Bengkalis of the ability of the ball (heading) relatively less with an average value of 42.89 and the ability to hold soccer ball (passing) classified as moderate by category being with an average of 47.54 and from dribbling ability (dribbling) classified as good with the average value 64.54, and from the ability to kick a ball (shooting) is quite with an average 54.60. Based on the basic techniques of football skills Team SMPN 2 Bengkalis District of Bengkalis quite enough with an average value of 53Keywords : Tinjauan, Tekhnik Dasar Sepakbola